TRACTATE ON HOUSEHOLD AND FARM - Ševarlić, Miladin M. (Economics of Agriculture, 2006)
In this paper work author continues and expands deliberation on semantic and methodological remarks, dilemmas and controversies regarding concepts of household and farm, as his contribution and incentive to other authors to make their own contributions in order to confirm, improve, increase or disprove the author's and other opinions on concepts of household and farm – two heterogeneous but mutually connected notions in agroeconomic theory and practice, as well as on syntagms emanated or connected with these two concepts.